Polyethylene with MoS2 nanoparticles toward antibacterial active packaging. Issue 3 (5th November 2022) - Castillo, Pedro; Goñi‐Ciaurriz, Leire; Olate‐Moya, Felipe; Bastías, Roberto; Farias, Sara; Palza, Humberto
Abstract: Molybdenum disulfide (MoS2 ) nanoparticles, obtained from liquid phase exfoliation in the presence of chitosan, were melt mixed with a linear low‐density polyethylene (LLDPE) matrix to produce novel antimicrobial active packaging materials. The LLDPE/MoS2 composites presented exfoliated nanoparticles forming aggregates that are well dispersed in the polymer matrix. These 2D‐layered MoS2 nanoparticles at concentrations of 0.5, 1.0, and 3.0 wt% rendered several functionalities to the LLDPE, as for example an antimicrobial behavior against Salmonella typhi and Listeria monocytogenes bacteria that can be explained not only by the photoactivity of the filler but also by changes in the composite surface. For instance, the composites presented a reduction in the water contact angle (i.e., an increased hydrophilicity) and relevant changes in the surface topography (i.e., reduced roughness) as compared with pure LLDPE. Regarding the barrier properties, while MoS2 dramatically increased the water vapor permeation (WVP) of the polymer matrix, until 15 times for composite with 3.0 wt% of filler, the oxygen permeation decreased around 25%. All these novel functionalities in the nanocomposites were obtained without significantly affecting the tensile mechanical properties of the pure LLDPE matrix. These results show that MoS2 is a promising filler for the development of antibacterial active packaging films with behaviors as similar as other 2D‐layered fillers such as graphene derivatives. Abstract : Multifunctional polymer composites with layered MoS2 particles.